2013
DOI: 10.1111/pin.12089
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of thoracic endometriosis

Abstract: Thoracic endometriosis is a rare disease responsible for catamenial pneumothorax. The immunohistochemical features of thoracic endometriosis are not well understood. An immunohistochemical examination of 84 diaphragmatic specimens of catamenial pneumothorax using antibodies against estrogen receptor (ER), progesterone receptor (PgR), CD10 and smooth muscle actin (SMA) was conducted. The endometrial tissue was small, and focally located around the chasm of the tendon on the side of the thoracic cavity. Endometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…The SMM is frequently found in peritoneal, [17][18][19][20] deep, 19,29,30 ovarian, 17,20,31,32 extragenital, 33,34 and pleuropulmonary endometriosis 35 as well as in adenomyosis. 36 The possibility of stromal cells differentiating into SMC, as happened in physiological SMM in the junctional zone of the uterus, 37,38 has been entertained 20,30 but nonetheless dismissed due to insufficient evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The SMM is frequently found in peritoneal, [17][18][19][20] deep, 19,29,30 ovarian, 17,20,31,32 extragenital, 33,34 and pleuropulmonary endometriosis 35 as well as in adenomyosis. 36 The possibility of stromal cells differentiating into SMC, as happened in physiological SMM in the junctional zone of the uterus, 37,38 has been entertained 20,30 but nonetheless dismissed due to insufficient evidence.…”
Section: Discussionmentioning
confidence: 99%
“…72 The pathological diagnosis of TE can be challenging, because lesions are sometimes so small that glands may not be identified. 88 Positive histopathological confirmation has been reported to range from 57% to 87.5% 68,71,73,83,84,[89][90][91] . Furthermore, sometimes it is difficult to distinguish endometrial stroma and inflammatory cells by hematoxylin and eosin staining.…”
Section: Catamenial Pneumothorax and Endometriosisrelated Pneumothomentioning
confidence: 99%
“…We could not find any significant difference in the rates of visceral pleural endometriosis. This result is probably due to the difficulty of inspecting for thoracic endometriosis, because these endometriotic implants are very small, as we reported previously . When ectopic endometrial sites are found in the parietal or visceral pleura, the endometrial tissues may extend to both the parietal and visceral pleural surfaces.…”
Section: Discussionmentioning
confidence: 71%